PENGARUH PEMBERDAYAAN DAN PELATIHAN TERHADAP KINERJA PELAKU USAHA MIKRO KECIL DAN MENENGAH BINAAN PUSAT LAYANAN USAHA TERPADU KUMKM PROVINSI MALUKU (STUDI KASUS UMKM KOTA AMBON) - Afriati Wattiheluw (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2019)
This study aims to determine and analyze the Empowerment and TrainingEffect on the performance of micro and small and medium entrepreneurs underthe guidance of the KUMKM Integrated Business Service Center in MalukuProvince (Case Study on Ambon City MSMEs). The hypotheses formulated inthis study are (1) Empowerment has a positive effect on the performance of micro,small and medium entrepreneurs under the guidance of the KUMKM IntegratedBusiness Service Center in Maluku Province. KUMKM Maluku Province (3)Empowerment and Training jointly have a positive influence on the performanceof micro and small and medium entrepreneurs under the guidance of the KUMKMIntegrated Business Service Center in Maluku Province. The data collected in thisstudy will then be analyzed using multiple linear regression analysis.The results of the study show that: (1) Empowerment has a significant positiveeffect on the performance of micro and small and medium entrepreneurs underthe guidance of the KUMKM Integrated Business Service Center in MalukuProvince as indicated by a value of 0.0015. (2) Training significantly has apositive influence on the performance of micro and small and mediumentrepreneurs under the guidance of the KUMKM Integrated Business ServiceCenter in Maluku Province as indicated by a value of 0.031. (3) Empowermentand Training together have a significant effect on the performance of micro andsmall and medium entrepreneurs under the guidance of the KUMKM IntegratedBusiness Service Center in Maluku Province as indicated by a value of 0.001, thusthe three hypotheses formulated in this study are accepted.